Framework for Implementing e-Portfolio Assessment to Improve Student Habits of Mind and Mastery of Chemistry Studies Concepts - Mahardika, Ilham; ., Nahadi; Firman, Harry (KnE Social Sciences, 2024)
The COVID-19 pandemic emphasized the need for improving teachers’ online teaching skills. One skill was using electronic portfolio assessment. Electronic portfolio assessment as an alternative assessment does not only focus on cognitive aspects but also is in line with the regulations of the Ministry of Education regarding the assessment of learning outcomes that focus not only on cognitive aspects but also on aspects of skills and attitudes. This study aimed to develop a framework for electronic portfolio assessment to improve students’ habits of mind and mastery of chemical studies concepts. We conducted a literature review to identify, categorize, synthesize and develop a framwork. This offers chemistry teachers a model for systematically designing and implementing an electronic portfolio of assessments and provides them with the instruments to conduct further research on assessment techniques. This framework guides chemistry teachers through important technical decisions, such as setting goals, identifying clear goals and establishing meaningful criteria for electronic portfolio assessment. Other issues discussed include defining the content of the electronic portfolio, managing the electronic portfolio, and monitoring and evaluating processes. Keywords: electronic portfolio assessment, habits, chemical concepts